A Critical Approach to Prophetic Traditions: Contextual Criticism in Understanding Hadith - Wasman Wasman; Mesraini Mesraini; Suwendi Suwendi (Al-Jami'ah: Journal of Islamic Studies, 2023)
Hadith scholars have developed a rigorous discipline for studying and examining the validity of writings attributed to the Prophet Muhammad. Significant research has been published on hadith with respect to its narration (sanad) and text or content (matn). What remains underdeveloped is the role of substantive criticism of the validity of hadith. This article examines the discourse of hadith criticism and provide analytical description and a critical approach for how the validity of a hadith can be determined. It argues that substantive criticism is necessary for proper and acceptable understanding of hadith and in turn for determining the validity of hadith. In addition to a methodology for hadith criticism, the article examines how the meaning of hadith is important in the hadith studies. The article’s main argument concerns the significance of contextual understanding of hadith in any critical study of hadith.